Design of polyaspartic acid peptide-poly (ethylene glycol)-poly (ε-caprolactone) nanoparticles as a carrier of hydrophobic drugs targeting cancer metastasized to bone - Liu JS (Dove Medical Press, 2017)
Jinsong Liu,1,* Youyun Zeng,1,* Shuai Shi,2 Lihua Xu,3 Hualin Zhang,4 Janak L Pathak,5 Yihuai Pan1 1School and Hospital of Stomatology, 2Institute of Biomedical Engineering, School of Ophthalmology & Optometry and Eye Hospital, Wenzhou Medical University, 3The First Affiliated Hospital of Wenzhou Medical University, Wenzhou, 4College of Stomatology, Ningxia Medical University, Yinchuan, 5School of Pharmaceutical Science and Technology, Health Sciences Platform, Tianjin University, Tianjin, People’s Republic of China *These authors contributed equally to this work Abstract: Treatment of cancer metastasized to bone is still a challenge due to hydrophobicity, instability, and lack of target specificity of anticancer drugs. Poly (ethylene glycol)-poly (e-caprolactone) polymer (PEG-PCL) is an effective, biodegradable, and biocompatible hydrophobic drug carrier, but lacks bone specificity. Polyaspartic acid with eight peptide sequences, that is, (Asp)8, has a strong affinity to bone surface. The aim of this study was to synthesize (Asp)8-PEG-PCL nanoparticles as a bone-specific carrier of hydrophobic drugs to treat cancer metastasized to bone. 1H nuclear magnetic resonance, Fourier transform infrared spectroscopy, and transmission electron microscopy data showed that (Asp)8-PEG-PCL nanoparticles (size 100 nm) were synthesized successfully. (Asp)8-PEG-PCL nanoparticles did not promote erythrocyte aggregation. Fluorescence microscopy showed clear uptake of Nile red-loaded (Asp)8-PEG-PCL nanoparticles by cancer cells. (Asp)8-PEG-PCL nanoparticles did not show cytotoxic effect on MG63 and human umbilical vein endothelial cells at the concentration of 10–800 µg/mL. (Asp)8-PEG-PCL nanoparticles bound with hydroxyapatite 2-fold more than PEG-PCL. Intravenously injected (Asp)8-PEG-PCL nanoparticles accumulated 2.7-fold more on mice tibial bone, in comparison to PEG-PCL. Curcumin is a hydrophobic anticancer drug with bone anabolic properties. Curcumin was loaded in the (Asp)8-PEG-PCL. (Asp)8-PEG-PCL showed 11.07% loading capacity and 95.91% encapsulation efficiency of curcumin. The curcumin-loaded (Asp)8-PEG-PCL nanoparticles gave sustained release of curcumin in high dose for >8 days. The curcumin-loaded (Asp)8-PEG-PCL nanoparticles showed strong antitumorigenic effect on MG63, MCF7, and HeLa cancer cells. In conclusion, (Asp)8-PEG-PCL nanoparticles were biocompatible, permeable in cells, a potent carrier, and an efficient releaser of hydrophobic anticancer drug and were bone specific. The curcumin-loaded (Asp)8-PEG-PCL nanoparticles showed strong antitumorigenic ability in vitro. Therefore, (Asp)8-PEG-PCL nanoparticles could be a potent carrier of hydrophobic anticancer drugs to treat the cancer metastasized to bone. Keywords: bone-targeting nanoparticles, polyaspartic acid peptides, PEG-PCL, cancer metastasized to bone, hydrophobic anticancer drug, curcumin